Two new combinatorial problems involving dominating sets for lottery schemes - Grundlingh, Werner R. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD (Mathematical Sciences. Applied Mathematics))--University of Stellenbosch, 2004.